Potret Perundungan dalam Novel Alaska Letta Karya Didik Sabrullah - Azizah, Azizah; Hayati, Yenni (Universitas Negeri Padang, 2024)
This research aims to determine the forms of bullying in the novel Alaska Aletta by Didik Sabrullah, the factors that cause bullying in the novel Alaska Aletta, and the impact of bullying in the novel Alaska Aletta. This research uses the theory of literary sociology studies. This research is literary research using descriptive methods. The data source for this research is the novel Alaska Aletta by Didik Sabrullah. The results of this research are forms of bullying, namely (a) physical bullying, (b) verbal, and (c) psychological. The factors that cause bullying are divided into two, namely (a) family influence factors and (b) peer influence factors. There are two impacts of bullying, namely, (a) individual impact and (c) social impact.